Pluralisme Agama dalam Al-Qur’an Telaah atas Penafsiran Farid Esack - Muhammad Fatih (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2020)
One of the issues that received considerable and dominant attention was the issue of diversity or religious plurality. This issue is a phenomenon that exists in the midst of the diversity of claims of absolute truth (Absolute Truth Claims) between religions that are contradicting one another. Each religion claims to be the truest and all others are heretical. This claim then gave birth to the belief commonly called the